Brown tumor in a patient with ectopic mediastinal parathyroid adenoma: A case report - Qari, Faiza A. (Saudi Dent J, 2014)
Brown tumors are uncommon focal giant-cell lesions that arise as a direct result of the effect of parathyroid hormone on bone tissue in some patients that have hyperparathyroidism. Primary hyperparathyroidism could be caused by ectopic mediastinal parathyroid adenomas. The occurrence of lesions is explainable on embryologic basis. We present a 55-year-old Saudi woman with a rare case of brown tumor of the maxilla due to ectopic mediastinal parathyroid adenoma.